2007
DOI: 10.1080/13607860600963539
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate treatment of people with dementia in residential and day care

Abstract: Dependence on the help provided by other people increases the risk of a person being inappropriately treated. Our objective was to investigate inappropriate treatment and its context in the care of people with dementia. Some 85 clients across eight care units providing dementia care were observed by means of a structured Dementia Care Mapping method (DCM). Of the 17 DCM categories for inappropriate treatment, withholding, invalidation, and objectification were the categories coded most frequently. Inappropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In a study by Winslow [30], in which 21 dementia family caregivers were asked in an open question about the quality of various community services on offer, including day care, the utilisation of day care was in second place. Sormunen et al [31] observed quality aspects using Dementia Care Mapping of 85 dementia patients in either residential or day care units.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Winslow [30], in which 21 dementia family caregivers were asked in an open question about the quality of various community services on offer, including day care, the utilisation of day care was in second place. Sormunen et al [31] observed quality aspects using Dementia Care Mapping of 85 dementia patients in either residential or day care units.…”
Section: Discussionmentioning
confidence: 99%
“…The demanding workloads of staff caring for people with dementia are commonly viewed as leading to higher levels of strain and lower levels of satisfaction than staff in mainstream LTC settings (Brodaty et al, 2003). Work pressures have also been shown to result in a more detached way of working whereby the psychological needs of residents are not recognised or permitted to impede staff members' ability to complete their allocated tasks (Sormunen et al, 2007). Within the three units it was evident that routine practice dominated and residents were afforded few opportunities to influence the routine.…”
Section: Workloadsmentioning
confidence: 99%
“…This skill mix is reflected in the facilities from which the study sample was drawn. The importance of well trained and supported LTC staff is constantly reiterated in the literature and is seen as an essential component in attaining good quality dementia specific care (Alzheimer's Australia, 2010;Lai et al, 2007;Sormunen et al, 2007). The staff rated their ability to manage their daily resident interactions highly in stark contrast to the practical examples they gave of their day-to-day work practice.…”
Section: Proficiency and Quality Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…In this way, clothes play a role in preserving continuity of the self. Ugly clothing is associated with the risk that the wearer will be poorly viewed and treated [12], but it may also mean that the bearer might feel being unworthy. Forced use of institutional clothing is likely to affect the self.…”
Section: Photomentioning
confidence: 99%